2010
DOI: 10.1126/science.1185723
|View full text |Cite
|
Sign up to set email alerts
|

Plectasin, a Fungal Defensin, Targets the Bacterial Cell Wall Precursor Lipid II

Abstract: Host defense peptides such as defensins are components of innate immunity and have retained antibiotic activity throughout evolution. Their activity is thought to be due to amphipathic structures, which enable binding and disruption of microbial cytoplasmic membranes. Contrary to this, we show that plectasin, a fungal defensin, acts by directly binding the bacterial cell-wall precursor Lipid II. A wide range of genetic and biochemical approaches identify cell-wall biosynthesis as the pathway targeted by plecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
462
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 475 publications
(486 citation statements)
references
References 20 publications
19
462
3
2
Order By: Relevance
“…In marked contrast, oyster Cg-Defs even at lethal concentrations (10 × MIC) did not compromise the membrane integrity of bacteria, but inhibited peptidoglycan biosynthesis by binding to lipid II (Schmitt et al, 2010). Likewise, Schneider et al (2010) recently demonstrated that a fungal defensin (plectasin) exhibited a similar mechanism of action. In the present study, SEM experiment revealed that rVpDef induced a remarkable modification of cell surface morphology, while the original ball shape was still recognizable (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In marked contrast, oyster Cg-Defs even at lethal concentrations (10 × MIC) did not compromise the membrane integrity of bacteria, but inhibited peptidoglycan biosynthesis by binding to lipid II (Schmitt et al, 2010). Likewise, Schneider et al (2010) recently demonstrated that a fungal defensin (plectasin) exhibited a similar mechanism of action. In the present study, SEM experiment revealed that rVpDef induced a remarkable modification of cell surface morphology, while the original ball shape was still recognizable (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…This was also in agreement with the fluorescence microscopy data (Figs 6 and 7). However, treatment of Bacillus subtilis with plectasin induced severe cell shape deformations (Schneider et al, 2010), which indicated the different modes of action for plectasin compared with rVpDef. 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the positively charged R 63 and R 64 perhaps increase the binding ability of peptide to the bacteria. It had been demonstrated that positively charged amino acids on the surface of the defensin could greatly improve their antibacterial activity, probably by promoting a better binding to the cell wall or membrane of target bacteria [49,50]. Therefore, the positively selected amino acids might have a functional relevance by modifying the charge distribution of Rpdefs.…”
Section: Discussionmentioning
confidence: 99%
“…The putative signal peptide of Rpdef1, Rpdef2 and Rpdef3 was identified at the N-terminal sequence with the first 24 amino acids, while the putative signal peptide of Rpdef4 comprised of the first 21 residues. The mature peptide of Rpdef1, Rpdef2, Rpdef3 and Rpdef4 consisted of 49 …”
Section: Sequence Analysis Of Rpdefsmentioning
confidence: 99%